Unexpected distribution of the 4-formylaminooxyvinylglycine (FVG) biosynthetic pathway in Pseudomonas and beyond. - Edward W Davis; Rachel A Okrent; Viola A Manning; Kristin M Trippe (PLoS ONE, 2021)
The biological herbicide and antibiotic 4-formylaminooxyvinylglycine (FVG) was originally isolated from several rhizosphere-associated strains of Pseudomonas fluorescens. Biosynthesis of FVG is dependent on the gvg biosynthetic gene cluster in P. fluorescens. In this investigation, we used comparative genomics to identify strains with the genetic potential to produce FVG due to presence of a gvg gene cluster. These strains primarily belong to two groups of Pseudomonas, P. fluorescens and P. syringae, however, a few strains with the gvg cluster were found outside of Pseudomonas. Mass spectrometry confirmed that all tested strains of the P. fluorescens species group produced FVG. However, P. syringae strains did not produce FVG under standard conditions. Several lines of evidence regarding the transmission of the gvg cluster including a robust phylogenetic analysis suggest that it was introduced multiple times through horizontal gene transfer within the Pseudomonas lineage as well as in select lineages of Thiomonas, Burkholderia and Pantoea. Together, these data broaden our understanding of the evolution and diversity of FVG biosynthesis. In the course of this investigation, additional gene clusters containing only a subset of the genes required to produce FVG were identified in a broad range of bacteria, including many non-pseudomonads.